Super-hydrophobic antifouling self-cleaning coating and preparation method thereof
Through the preparation methods of modified graphene oxide and modified nano-silica, the problem of insufficient hydrophobic properties of existing fluorocarbon coatings is solved, and the superhydrophobicity and self-cleaning properties of the coatings are realized. It is suitable for high weather resistance requirements. environment.
Patent Information
- Application Number
- CN202411575746.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing fluorocarbon coatings have poor hydrophobic properties and the dispersion of nanoparticles have not been effectively solved.
By preparing modified graphene oxide and modified nano-silica, additives such as γ-methacryloyloxypropyltrimethoxysilane and octyltriethoxysilane are used to improve graphene oxide and The hydrophobicity of silica and the formation of chemical bonds improves its dispersion and binding force in fluorocarbon resin.
It significantly improves the hydrophobicity and anti-fouling properties of the coating, and forms a coating with superhydrophobicity, self-cleaning and excellent anti-corrosion properties, which is suitable for environments that are subject to long-term rainwater erosion and seawater corrosion.
Smart Images

Figure QLYQS_1 
Figure BDA0005121751960000021 
Figure BDA0005121751960000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a super-hydrophobic anti-fouling self-cleaning coating and a preparation method thereof. Background Art
[0002] Fluorocarbon coating refers to coating with fluorine resin as the main film-forming substance; it is also called fluorocarbon paint, fluorine coating, fluorine resin coating, etc. Among various coatings, fluororesin coating has particularly superior properties due to the large electronegativity of the introduced fluorine element and the strong carbon-fluorine bond energy. It has weather resistance, heat resistance, low temperature resistance, chemical resistance, and unique non-stickiness and low friction.
[0003] As the requirements for building lifespan become increasingly higher, the water resistance, pollution resistance, and salt spray resistance of coatings on some building surfaces that are frequently exposed to rainwater erosion, such as the seawater corrosion parts of cross-sea bridges and ships, still need to be improved.
[0004] For example, CN100554343C discloses a nano-titanium dioxide modified fluorocarbon coating, and its preparation process and application. The coating is prepared by adding a mixture of anatase nano-TiO2 and rutile nano-TiO2 to an existing fluorocarbon coating, and the addition ratio is: the weight ratio of the mixture of anatase nano-TiO2 and rutile nano-TiO2: fluorocarbon coating is 1-4:100; in the mixture of anatase nano-TiO2 and rutile nano-TiO2, the weight ratio of anatase nano-TiO2 to rutile nano-TiO2 is 4:1.
[0005] For example, CN113637368B discloses a fluorocarbon coating and its preparation method and application, which belongs to the technical field of coating preparation. The fluorocarbon coating is prepared by mixing component A and component B in a mass ratio of 10:(0.8-1); the component A includes 60-65 parts of fluorocarbon resin, 5-10 parts of modified whisker zinc oxide, 5-10 parts of modified nano silicon dioxide, 0.3-0.5 parts of zinc molybdate, 4-8 parts of zinc borate, 0.3-0.5 parts of zinc sulfate, 0.5-1.8 parts of dispersant, 0.2-0.5 parts of leveling agent, 0.1-0.3 parts of defoamer and 12-14 parts of solvent.
[0006] However, the above patents all simply add nanoparticles to fillers to improve the roughness of the coating and improve the hydrophobicity of the coating, but do not take into account the dispersibility of the nanoparticles and other issues. The present invention is hereby proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a super hydrophobic antifouling self-cleaning coating and a preparation method thereof in order to overcome the weak hydrophobicity of the coating in the above-mentioned prior art.
[0008] In the prior art, the hydrophobicity of fluorocarbon coatings is generally improved by adding hydrophobic additives such as silane coupling agents, or by using the roughness of nanoparticles to improve the hydrophobicity. Simply adding additives has limited improvement on the hydrophobicity, and the addition of nanoparticles also needs to consider issues such as dispersibility.
[0009] Therefore, the first aspect of the present invention provides a super hydrophobic antifouling self-cleaning coating, comprising the following components in parts by weight:
[0010]
[0011] The modified graphene oxide is prepared by modifying graphene oxide with γ-methacryloxypropyltrimethoxysilane;
[0012] The modified nano silicon dioxide is prepared by modifying silicon dioxide with octyltriethoxysilane and nonafluorohexyltriethoxysilane.
[0013] Preferably, the modified graphene oxide is prepared by the following steps:
[0014] Graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution are uniformly mixed, stirred and filtered to obtain modified graphene oxide.
[0015] Preferably, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:(1-5):(100-300).
[0016] Preferably, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:2:200.
[0017] Preferably, the mass ratio of anhydrous ethanol to water in the ethanol aqueous solution is 1:1.
[0018] Preferably, the specific conditions of the stirring are:
[0019] Stir at 400-800 rpm for 4-8 hours at 50-80°C.
[0020] Preferably, the specific conditions of the stirring are:
[0021] The mixture was stirred at 600 rpm at 60°C for 6 h.
[0022] Preferably, the modified nano-silica is prepared by the following steps:
[0023] Octyltriethoxysilane and nonafluorohexyltriethoxysilane are dissolved in ethanol, the pH is adjusted to 4-6, and stirred for a primary reaction to obtain a liquid phase. Then, silicon dioxide is dispersed in ethanol and added to the liquid phase, the pH is adjusted to 10-12, and stirred for a secondary reaction. After centrifugal washing and drying, modified nano silicon dioxide is obtained.
[0024] Preferably, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:(4-8).
[0025] Preferably, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:6.
[0026] Preferably, the time of the primary reaction is 30-40 minutes and the temperature is 20-40°C.
[0027] Preferably, the time of the primary reaction is 35 min and the temperature is 30°C.
[0028] Preferably, the reagent used to adjust the pH to 4-6 is acetic acid, and the solvent used to adjust the pH to 10-12 is ammonium hydroxide.
[0029] Preferably, the secondary reaction time is 18-36 hours and the temperature is 20-40°C.
[0030] Preferably, the secondary reaction time is 24 hours and the temperature is 30°C.
[0031] Preferably, the fluorocarbon resin is one or more of HLR-6, HLR-7, HLR-670, ZHM-2, ZHM-5, and ZHM-70.
[0032] Preferably, the fluorocarbon resin is HLR-6.
[0033] Preferably, the curing agent is one or more of aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate.
[0034] Preferably, the curing agent is aliphatic polyisocyanate.
[0035] Preferably, the dispersant is one or more of BYK-110, BYK-161, Nuosperse FX600, SDA120, SDA-150, and SDA-170.
[0036] Preferably, the leveling agent is one or more of EFKA-3777, HY-3777, FC-4430, and AKN-1377.
[0037] Preferably, the defoamer is a higher alcohol defoamer or a silicone defoamer.
[0038] Preferably, the solvent is one or more of xylene, butyl acetate, propylene glycol methyl ether acetate, and ethylene glycol ethyl ether acetate.
[0039] A second aspect of the present invention provides a method for preparing a super hydrophobic antifouling self-cleaning coating, comprising the following steps:
[0040] S1, mixing graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution uniformly, stirring and filtering to obtain modified graphene oxide;
[0041] S2, dissolving octyltriethoxysilane and nonafluorohexyltriethoxysilane in ethanol, adjusting the pH to 4-6, stirring for a primary reaction to obtain a liquid phase, dispersing silicon dioxide in ethanol and adding it to the liquid phase, adjusting the pH to 10-12, stirring for a secondary reaction, and centrifugally washing and drying to obtain modified nano-silicon dioxide;
[0042] S3, 20-50 parts of fluorocarbon resin and 30-60 parts of solvent are mixed evenly, and then 5-15 parts of curing agent, 1-5 parts of dispersant, 1-5 parts of leveling agent, 1-5 parts of defoaming agent, 1-10 parts of modified graphene oxide and 1-10 parts of modified nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0043] Preferably, in step S1, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:(1-5):(100-300).
[0044] Preferably, in step S1, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:2:200.
[0045] Preferably, in step S1, the mass ratio of anhydrous ethanol to water in the ethanol aqueous solution is 1:1.
[0046] Preferably, in step S1, the specific conditions of the stirring are:
[0047] Stir at 400-800 rpm for 4-8 hours at 50-80°C.
[0048] Preferably, in step S1, the specific conditions of the stirring are:
[0049] The mixture was stirred at 600 rpm at 60°C for 6 h.
[0050] Preferably, in step S2, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:(4-8).
[0051] Preferably, in step S2, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:6.
[0052] Preferably, in step S2, the time of the primary reaction is 30-40 min and the temperature is 20-40°C.
[0053] Preferably, in step S2, the time of the primary reaction is 35 min and the temperature is 30°C.
[0054] Preferably, in step S2, the reagent used to adjust the pH to 4-6 is acetic acid, and the solvent used to adjust the pH to 10-12 is ammonium hydroxide.
[0055] Preferably, in step S2, the secondary reaction is carried out for 18-36 hours at a temperature of 20-40°C.
[0056] Preferably, in step S2, the secondary reaction is carried out for 24 hours at a temperature of 30°C.
[0057] Preferably, in step S3, the fluorocarbon resin is one or more of HLR-6, HLR-7, HLR-670, ZHM-2, ZHM-5, and ZHM-70.
[0058] Preferably, in step S3, the fluorocarbon resin is HLR-6.
[0059] Preferably, in step S3, the curing agent is one or more of aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate.
[0060] Preferably, in step S3, the curing agent is aliphatic polyisocyanate.
[0061] Preferably, in step S3, the dispersant is one or more of BYK-110, BYK-161, Nuosperse FX600, SDA120, SDA-150, and SDA-170.
[0062] Preferably, in step S3, the leveling agent is one or more of EFKA-3777, HY-3777, FC-4430, and AKN-1377.
[0063] Preferably, in step S3, the defoaming agent is a high carbon alcohol defoaming agent or a silicone defoaming agent.
[0064] Preferably, in step S3, the solvent is one or more of xylene, butyl acetate, propylene glycol methyl ether acetate, and ethylene glycol ethyl ether acetate.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] 1. Compared with the prior art, the trimethoxysilane at one end of the γ-methacryloxypropyltrimethoxysilane in the present invention can be hydrolyzed to form silanol groups, which react with oxygen-containing functional groups such as hydroxyl groups and carboxyl groups on the surface of graphene oxide to form a condensation reaction, thereby firmly grafting to the surface of graphene oxide to modify the graphene oxide, and the methacryloxy group at the other end is a reactive unsaturated double bond group, which can react chemically with the unsaturated double bonds in the polymer matrix (fluorocarbon resin) to form a chemical bond connection between the graphene oxide and the polymer matrix, greatly improving the interfacial bonding force between the two, thereby making the modified graphene oxide uniformly dispersed in the polymer matrix, and after the γ-methacryloxypropyltrimethoxysilane modifies the graphene oxide, its non-polar organic group increases the hydrophobicity of the graphene oxide, thereby improving its solubility in organic solvents, and at the same time, it is easier to be uniformly dispersed in the polymer matrix, avoiding the occurrence of agglomeration, which is conducive to the preparation of a composite material with uniform and stable performance, and the hydrophobicity of the formed coating is enhanced. In addition, graphene oxide has a flaky structure and can form a tight barrier layer in the coating, preventing corrosive media such as oxygen, water, and chloride ions from penetrating into the surface of the coated object, thereby delaying the corrosion process of metal and other substrates. This physical barrier effect can significantly improve the anti-corrosion ability of the coating and extend the service life of the protected material.
[0067] 2. Compared with the prior art, the nonafluorohexyl triethoxysilane in the present invention has a specific fluorinated group and an ethoxy group, which can react with the hydroxyl group on the surface of silicon dioxide to form a chemical bond. Through the chemical reaction, the ethoxy group of nonafluorohexyl triethoxysilane reacts with the hydroxyl group on the surface of silicon dioxide to introduce the fluorinated group to the surface of silicon dioxide, thereby reducing its surface energy and making it have super hydrophobic properties. At the same time, octyl triethoxysilane has a long carbon chain structure, and its hydrolysis and condensation reaction conditions are mild. It is hydrolyzed into a silanol monomer, and the silanol hydroxyl group on the surface of the silanol monomer dehydrates and condenses with the silanol hydroxyl group on the surface of the silicon dioxide nanoparticle to form a Si-O-Si bond, thereby grafting on the surface of the silicon dioxide nanoparticle, constructing a surface roughness structure, forming a dense network structure, changing its hydrophilicity, and achieving the effect of hydrophobic modification. And because of the formation of Si-O-Si bonds, the silicon dioxide nanoparticles have positive charges, while the graphene oxide modified by γ-methacryloxypropyltrimethoxysilane has negative charges, and the two are adsorbed together by electrostatic attraction, and the methacryloxy group on the modified graphene oxide can form a covalent bond with the Si-O-Si bond, further improving the binding force between the modified nano silicon dioxide nanoparticles and the modified graphene oxide. In addition, because the modified graphene oxide is evenly dispersed in the polymer matrix, the modified nano silicon dioxide adsorbed thereon is also completely dispersed in the polymer matrix.
[0068] In addition, the flake structure of graphene oxide and the dense network structure of the surface of modified nano-silica are combined to form a three-dimensional network flake composite structure, which further prevents substances such as water, oxygen, and ions.
[0069] Therefore, nonafluorohexyltriethoxysilane and octyltriethoxysilane respectively reduce the surface energy of silica particles and construct a rough surface structure to make silica have excellent hydrophobic properties, and the excellent hydrophobic properties of modified graphene oxide synergistically achieve the superhydrophobicity of the coating formed by the coating. DETAILED DESCRIPTION
[0070] For ease of understanding of the present application, the present application will be described more fully below by way of embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0071] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0072] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" include the number, and the meaning of "multiple" in "one or more" is more than two.
[0073] In the prior art, the hydrophobicity of fluorocarbon coatings is generally improved by adding hydrophobic additives such as silane coupling agents, or by using the roughness of nanoparticles to improve the hydrophobicity. Simply adding additives has limited improvement on the hydrophobicity, and the addition of nanoparticles also needs to consider issues such as dispersibility.
[0074] Therefore, an optional embodiment of the present invention provides a super hydrophobic antifouling self-cleaning coating, comprising the following components in parts by weight:
[0075]
[0076] The modified graphene oxide is prepared by modifying graphene oxide with γ-methacryloxypropyltrimethoxysilane;
[0077] The modified nano silicon dioxide is prepared by modifying silicon dioxide with octyltriethoxysilane and nonafluorohexyltriethoxysilane.
[0078] In an optional embodiment, the modified graphene oxide is prepared by the following steps:
[0079] Graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution are uniformly mixed, stirred and filtered to obtain modified graphene oxide.
[0080] In an optional embodiment, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:(1-5):(100-300).
[0081] In an optional embodiment, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:2:200.
[0082] In an optional embodiment, the mass ratio of anhydrous ethanol to water in the ethanol aqueous solution is 1:1.
[0083] In an optional embodiment, the specific conditions of the stirring are:
[0084] Stir at 400-800 rpm for 4-8 hours at 50-80°C.
[0085] In an optional embodiment, the specific conditions of the stirring are:
[0086] The mixture was stirred at 600 rpm at 60°C for 6 h.
[0087] In some embodiments of the present invention, the trimethoxysilane at one end of the γ-methacryloxypropyltrimethoxysilane can be hydrolyzed to form silanol groups, which react with oxygen-containing functional groups such as hydroxyl groups and carboxyl groups on the surface of graphene oxide to form a condensation reaction, thereby firmly grafting to the surface of graphene oxide to modify the graphene oxide. The methacryloxy group at the other end is a reactive unsaturated double bond group that can react chemically with the unsaturated double bonds in the polymer matrix (fluorocarbon resin) to form a chemical bond connection between the graphene oxide and the polymer matrix, greatly improving the interfacial bonding force between the two, thereby making the modified graphene oxide uniformly dispersed in the polymer matrix. After the graphene oxide is modified by the γ-methacryloxypropyltrimethoxysilane, its non-polar organic group increases the hydrophobicity of the graphene oxide, thereby improving its solubility in organic solvents. At the same time, it is also easier to be uniformly dispersed in the polymer matrix, avoiding the occurrence of agglomeration, which is conducive to the preparation of a composite material with uniform and stable performance.
[0088] In an optional embodiment, the modified nano-silica is prepared by the following steps:
[0089] Octyltriethoxysilane and nonafluorohexyltriethoxysilane are dissolved in ethanol, the pH is adjusted to 4-6, and stirred for a primary reaction to obtain a liquid phase. Then, silicon dioxide is dispersed in ethanol and added to the liquid phase, the pH is adjusted to 10-12, and stirred for a secondary reaction. After centrifugal washing and drying, modified nano silicon dioxide is obtained.
[0090] In an optional embodiment, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:(4-8).
[0091] In an optional embodiment, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:6.
[0092] In an optional embodiment, the time of the primary reaction is 30-40 minutes and the temperature is 20-40°C.
[0093] In an optional embodiment, the time of the primary reaction is 35 minutes and the temperature is 30°C.
[0094] In an optional embodiment, the reagent used to adjust the pH to 4-6 is acetic acid, and the solvent used to adjust the pH to 10-12 is ammonium hydroxide.
[0095] In an optional embodiment, the secondary reaction time is 18-36 hours and the temperature is 20-40°C.
[0096] In an optional embodiment, the secondary reaction time is 24 hours and the temperature is 30°C.
[0097] In some embodiments of the present invention, nonafluorohexyl triethoxysilane has a specific fluorinated group and an ethoxy group, which can react with the hydroxyl group on the surface of silica to form a chemical bond. Through the chemical reaction, the ethoxy group of nonafluorohexyl triethoxysilane reacts with the hydroxyl group on the surface of silica to introduce the fluorinated group into the surface of silica, thereby reducing its surface energy and making it super hydrophobic. At the same time, octyl triethoxysilane has a long carbon chain structure, and its hydrolysis and condensation reaction conditions are mild. It is hydrolyzed into a silanol monomer, and the silanol hydroxyl group on the surface of the silanol monomer dehydrates and condenses with the silanol hydroxyl group on the surface of the silica nanoparticle to form a Si-O-Si bond, thereby grafting on the surface of the silica nanoparticle, constructing a surface roughness structure, changing its hydrophilicity, and achieving the effect of hydrophobic modification. And because of the formation of Si-O-Si bonds, the silicon dioxide nanoparticles have positive charges, while the graphene oxide modified by γ-methacryloxypropyltrimethoxysilane has negative charges, and the two are adsorbed together by electrostatic attraction, and the methacryloxy group on the modified graphene oxide can form a covalent bond with the Si-O-Si bond, further improving the binding force between the modified nano silicon dioxide nanoparticles and the modified graphene oxide. In addition, because the modified graphene oxide is evenly dispersed in the polymer matrix, the modified nano silicon dioxide adsorbed thereon is also completely dispersed in the polymer matrix.
[0098] Therefore, nonafluorohexyltriethoxysilane and octyltriethoxysilane respectively reduce the surface energy of silica particles and construct a rough surface structure to make silica have excellent hydrophobic properties, and the excellent hydrophobic properties of modified graphene oxide synergistically achieve the superhydrophobicity of the coating formed by the coating.
[0099] In an optional embodiment, the fluorocarbon resin is one or more of HLR-6, HLR-7, HLR-670, ZHM-2, ZHM-5, and ZHM-70.
[0100] In an optional embodiment, the fluorocarbon resin is HLR-6.
[0101] In an optional embodiment, the curing agent is one or more of aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate.
[0102] In an optional embodiment, the curing agent is an aliphatic polyisocyanate.
[0103] In an optional embodiment, the dispersant is one or more of BYK-110, BYK-161, Nuosperse FX600, SDA120, SDA-150, and SDA-170.
[0104] In an optional embodiment, the leveling agent is one or more of EFKA-3777, HY-3777, FC-4430, and AKN-1377.
[0105] In an optional embodiment, the defoaming agent is a high-carbon alcohol defoaming agent or a silicone defoaming agent.
[0106] In an optional embodiment, the solvent is one or more of xylene, butyl acetate, propylene glycol methyl ether acetate, and ethylene glycol ethyl ether acetate.
[0107] In an optional embodiment of the present invention, a method for preparing a super hydrophobic antifouling self-cleaning coating is also provided, comprising the following steps:
[0108] S1, mixing graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution uniformly, stirring and filtering to obtain modified graphene oxide;
[0109] S2, dissolving octyltriethoxysilane and nonafluorohexyltriethoxysilane in ethanol, adjusting the pH to 4-6, stirring for a primary reaction to obtain a liquid phase, dispersing silicon dioxide in ethanol and adding it to the liquid phase, adjusting the pH to 10-12, stirring for a secondary reaction, and centrifugally washing and drying to obtain modified nano-silicon dioxide;
[0110] S3, 20-50 parts of fluorocarbon resin and 30-60 parts of solvent are mixed evenly, and then 5-15 parts of curing agent, 1-5 parts of dispersant, 1-5 parts of leveling agent, 1-5 parts of defoaming agent, 1-10 parts of modified graphene oxide and 1-10 parts of modified nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0111] In an optional embodiment, in step S1, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:(1-5):(100-300).
[0112] In an optional embodiment, in step S1, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:2:200.
[0113] In an optional embodiment, in step S1, the mass ratio of anhydrous ethanol to water in the ethanol aqueous solution is 1:1.
[0114] In an optional embodiment, in step S1, the specific conditions of the stirring are:
[0115] Stir at 400-800 rpm for 4-8 hours at 50-80°C.
[0116] In an optional embodiment, in step S1, the specific conditions of the stirring are:
[0117] The mixture was stirred at 600 rpm at 60°C for 6 h.
[0118] In an optional embodiment, in step S2, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:(4-8).
[0119] In an optional embodiment, in step S2, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:6.
[0120] In an optional embodiment, in step S2, the time of the primary reaction is 30-40 minutes and the temperature is 20-40°C.
[0121] In an optional embodiment, in step S2, the time of the single reaction is 35 minutes and the temperature is 30°C.
[0122] In an optional embodiment, in step S2, the reagent used to adjust the pH to 4-6 is acetic acid, and the solvent used to adjust the pH to 10-12 is ammonium hydroxide.
[0123] In an optional embodiment, in step S2, the secondary reaction time is 18-36 hours and the temperature is 20-40°C.
[0124] In an optional embodiment, in step S2, the secondary reaction time is 24 hours and the temperature is 30°C.
[0125] In an optional embodiment, in step S3, the fluorocarbon resin is one or more of HLR-6, HLR-7, HLR-670, ZHM-2, ZHM-5, and ZHM-70.
[0126] In an optional embodiment, in step S3, the fluorocarbon resin is HLR-6.
[0127] In an optional embodiment, in step S3, the curing agent is one or more of aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate.
[0128] In an optional embodiment, in step S3, the curing agent is an aliphatic polyisocyanate.
[0129] In an optional embodiment, in step S3, the dispersant is one or more of BYK-110, BYK-161, NuosperseFX600, SDA120, SDA-150, and SDA-170.
[0130] In an optional embodiment, in step S3, the leveling agent is one or more of EFKA-3777, HY-3777, FC-4430, and AKN-1377.
[0131] In an optional embodiment, in step S3, the defoaming agent is a high-carbon alcohol defoaming agent or a silicone defoaming agent.
[0132] In an optional embodiment, in step S3, the solvent is one or more of xylene, butyl acetate, propylene glycol methyl ether acetate, and ethylene glycol ethyl ether acetate.
[0133] The super hydrophobic antifouling self-cleaning coating of the present invention is described in more detail below in conjunction with specific embodiments.
[0134] Example 1
[0135] This embodiment provides a method for preparing a super hydrophobic antifouling self-cleaning coating, comprising the following steps:
[0136] S1, 1 part of graphene oxide, 2 parts of γ-methacryloxypropyltrimethoxysilane, and 200 parts of ethanol aqueous solution (the mass ratio of anhydrous ethanol to water is 1:1) are mixed evenly, stirred at a speed of 600 rpm for 6 hours, and filtered to obtain modified graphene oxide;
[0137] S2, dissolving 1 part of octyltriethoxysilane and 1 part of nonafluorohexyltriethoxysilane in 50 parts of ethanol, adjusting the pH to 5 with acetic acid, stirring and reacting at 30°C for 35 minutes to obtain a liquid phase, dispersing 6 parts of silicon dioxide in 50 parts of ethanol and adding the silicon dioxide to the liquid phase, adjusting the pH to 11 with ammonium hydroxide, stirring and reacting at 30°C for 24 hours, and washing by centrifugation and drying to obtain modified nano-silica;
[0138] S3, 40 parts of fluorocarbon resin (HLR-6) and 50 parts of propylene glycol methyl ether acetate are mixed evenly, and then 10 parts of toluene diisocyanate, 2 parts of dispersant (BYK-110), 2 parts of leveling agent (EFKA-3777), 2 parts of silicone defoaming agent, 8 parts of modified graphene oxide and 8 parts of modified nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0139] Example 2
[0140] This embodiment provides a method for preparing a super hydrophobic antifouling self-cleaning coating, comprising the following steps:
[0141] S1, 1 part of graphene oxide, 2 parts of γ-methacryloxypropyltrimethoxysilane, and 200 parts of ethanol aqueous solution (the mass ratio of anhydrous ethanol to water is 1:1) are mixed evenly, stirred at a speed of 600 rpm for 6 hours, and filtered to obtain modified graphene oxide;
[0142] S2, dissolving 1 part of octyltriethoxysilane and 1 part of nonafluorohexyltriethoxysilane in 50 parts of ethanol, adjusting the pH to 5 with acetic acid, stirring and reacting at 30°C for 35 minutes to obtain a liquid phase, dispersing 6 parts of silicon dioxide in 50 parts of ethanol and adding the silicon dioxide to the liquid phase, adjusting the pH to 11 with ammonium hydroxide, stirring and reacting at 30°C for 24 hours, and washing by centrifugation and drying to obtain modified nano-silica;
[0143] S3, 28 parts of fluorocarbon resin (HLR-6) and 42 parts of propylene glycol methyl ether acetate are mixed evenly, and then 8 parts of toluene diisocyanate, 1 part of dispersant (BYK-110), 1 part of leveling agent (EFKA-3777), 1 part of silicone defoaming agent, 4 parts of modified graphene oxide and 4 parts of modified nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0144] Example 3
[0145] This embodiment provides a method for preparing a super hydrophobic antifouling self-cleaning coating, comprising the following steps:
[0146] S1, 1 part of graphene oxide, 2 parts of γ-methacryloxypropyltrimethoxysilane, and 200 parts of ethanol aqueous solution (the mass ratio of anhydrous ethanol to water is 1:1) are mixed evenly, stirred at a speed of 600 rpm for 6 hours, and filtered to obtain modified graphene oxide;
[0147] S2, dissolving 1 part of octyltriethoxysilane and 1 part of nonafluorohexyltriethoxysilane in 50 parts of ethanol, adjusting the pH to 5 with acetic acid, stirring and reacting at 30°C for 35 minutes to obtain a liquid phase, dispersing 6 parts of silicon dioxide in 50 parts of ethanol and adding the silicon dioxide to the liquid phase, adjusting the pH to 11 with ammonium hydroxide, stirring and reacting at 30°C for 24 hours, and washing by centrifugation and drying to obtain modified nano-silica;
[0148] S3, 48 parts of fluorocarbon resin (HLR-6) and 57 parts of propylene glycol methyl ether acetate are mixed evenly, and then 14 parts of toluene diisocyanate, 3 parts of dispersant (BYK-110), 3 parts of leveling agent (EFKA-3777), 3 parts of silicone defoaming agent, 10 parts of modified graphene oxide and 10 parts of modified nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0149] Comparative Example 1
[0150] This comparative example provides a method for preparing a coating, comprising the following steps:
[0151] S1, 1 part of graphene oxide, 2 parts of γ-methacryloxypropyltrimethoxysilane, and 200 parts of ethanol aqueous solution (the mass ratio of anhydrous ethanol to water is 1:1) are mixed evenly, stirred at a speed of 600 rpm for 6 hours, and filtered to obtain modified graphene oxide;
[0152] S3, 40 parts of fluorocarbon resin (HLR-6) and 50 parts of propylene glycol methyl ether acetate are mixed evenly, and then 10 parts of toluene diisocyanate, 2 parts of dispersant (BYK-110), 2 parts of leveling agent (EFKA-3777), 2 parts of silicone defoaming agent, and 16 parts of modified graphene oxide are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0153] Comparative Example 2
[0154] This comparative example provides a method for preparing a coating, comprising the following steps:
[0155] S1, dissolving 1 part of octyltriethoxysilane and 1 part of nonafluorohexyltriethoxysilane in 50 parts of ethanol, adjusting the pH to 5 with acetic acid, stirring and reacting at 30°C for 35 minutes to obtain a liquid phase, dispersing 6 parts of silicon dioxide in 50 parts of ethanol and adding the silicon dioxide to the liquid phase, adjusting the pH to 11 with ammonium hydroxide, stirring and reacting at 30°C for 24 hours, and washing by centrifugation and drying to obtain modified nano-silica;
[0156] S2, 40 parts of fluorocarbon resin (HLR-6) and 50 parts of propylene glycol methyl ether acetate are mixed evenly, and then 10 parts of toluene diisocyanate, 2 parts of dispersant (BYK-110), 2 parts of leveling agent (EFKA-3777), 2 parts of silicone defoaming agent, and 16 parts of modified nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0157] Comparative Example 3
[0158] This comparative example provides a method for preparing a coating, comprising the following steps:
[0159] S1, dissolving 1 part of octyltriethoxysilane and 1 part of nonafluorohexyltriethoxysilane in 50 parts of ethanol, adjusting the pH to 5 with acetic acid, stirring and reacting at 30°C for 35 minutes to obtain a liquid phase, dispersing 6 parts of silicon dioxide in 50 parts of ethanol and adding the silicon dioxide to the liquid phase, adjusting the pH to 11 with ammonium hydroxide, stirring and reacting at 30°C for 24 hours, and washing by centrifugation and drying to obtain modified nano-silica;
[0160] S2, 40 parts of fluorocarbon resin (HLR-6) and 50 parts of propylene glycol methyl ether acetate are mixed evenly, and then 10 parts of toluene diisocyanate, 2 parts of dispersant (BYK-110), 2 parts of leveling agent (EFKA-3777), 2 parts of silicone defoaming agent, 8 parts of graphene oxide and 8 parts of modified nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0161] Comparative Example 4
[0162] This comparative example provides a method for preparing a coating, comprising the following steps:
[0163] S1, 1 part of graphene oxide, 2 parts of γ-methacryloxypropyltrimethoxysilane, and 200 parts of ethanol aqueous solution (the mass ratio of anhydrous ethanol to water is 1:1) are mixed evenly, stirred at a speed of 600 rpm for 6 hours, and filtered to obtain modified graphene oxide;
[0164] S3, 40 parts of fluorocarbon resin (HLR-6) and 50 parts of propylene glycol methyl ether acetate are mixed evenly, and then 10 parts of toluene diisocyanate, 2 parts of dispersant (BYK-110), 2 parts of leveling agent (EFKA-3777), 2 parts of silicone defoaming agent, 8 parts of modified graphene oxide and 8 parts of nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0165] Comparative Example 5
[0166] This comparative example provides a method for preparing a coating, comprising the following steps:
[0167] Mix 40 parts of fluorocarbon resin (HLR-6) and 50 parts of propylene glycol methyl ether acetate evenly, then add 10 parts of toluene diisocyanate, 2 parts of dispersant (BYK-110), 2 parts of leveling agent (EFKA-3777), and 2 parts of silicone defoaming agent under stirring, and mix evenly to obtain a super hydrophobic antifouling self-cleaning coating.
[0168] The differences between modified graphene oxide and modified nano-silicon dioxide as fillers in the above embodiments and comparative examples are shown in 1 below.
[0169] Table 1 Types of fillers in Examples 1 to 3 and Comparative Examples 1 to 5
[0170] Examples Filler 1 Packing 2 Example 1 Modified graphene oxide Modified Nano Silica Example 2 Modified graphene oxide Modified Nano Silica Example 3 Modified graphene oxide Modified Nano Silica Comparative Example 1 Modified graphene oxide none Comparative Example 2 none Modified Nano Silica Comparative Example 3 Graphene oxide Modified Nano Silica Comparative Example 4 Modified graphene oxide Nano Silica Comparative Example 5 none none
[0171] Test Case
[0172] The compositions of Examples 1 to 3 and Comparative Examples 1 to 5 are applied onto a metal substrate and cured to obtain a coating.
[0173] 1. Adhesion test
[0174] Test method: Use a blade or a grid cutter to make 100 small squares with a spacing of 1mm on the coating in a criss-cross pattern, scratching deep into the metal substrate and removing the burrs on the scratches. Cover the scratched area with adhesive tape (brand 3M 610 or Yongda) at a 45° angle along the 100 grids, flatten the tape so that there are no bubbles between the tape and the coating, pull the two ends of the tape, and quickly peel off the tape at a 90° angle to the surface of the test plate. No coating will fall off. Repeat three times.
[0175] 2. Water contact angle test
[0176] The contact angle refers to the angle θ between the tangent of the gas-liquid interface at the intersection of the gas, liquid and solid phases, passing through the liquid and the solid-liquid boundary line. It is a measure of the degree of wettability. If θ<90°, the solid surface is hydrophilic, that is, the liquid is easier to wet the solid. The smaller the contact angle, the more water spreads on the surface of the substrate, and the easier it is to clean. If θ>90°, the solid surface is hydrophobic, that is, the liquid is not easy to wet the solid and is easy to move on the surface.
[0177] 3. Cleaning performance test
[0178] Apply oil stains to the surface of the coated stainless steel substrate and cure it at room temperature for 10 days. Then wipe it with a rag dipped in clean water and then wipe it dry with a dry rag. If there is no stain residue on the surface, it is recorded as Level 1. If there is a small amount of stain residue on the surface, it is recorded as Level 2. If there is a large amount of stain residue on the surface, it is recorded as Level 3.
[0179] 4. Acid resistance
[0180] According to GB / T 1763-1979, soak at 23±2℃ for 120h, no blistering, wrinkling or color spot, slight gloss loss and color change are allowed.
[0181] 5. Alkali resistance
[0182] According to GB / T 1763-1979, soak at 23±2℃ for 720h, no blistering, wrinkling or color spot, slight gloss loss and color change are allowed.
[0183] 6. Salt spray resistance: According to GB / T 1771-2007, 600h (the rust width on one side of the scratch is ≤2mm, and there are no bubbles, rust or shedding on the other board surfaces 5mm away from the scratch.)
[0184] The test results are shown in Table 2 below.
[0185] Table 2 Water resistance and contact angle test results of coatings
[0186] Examples Adhesion Contact angle Cleanability Acid resistance Alkali resistance Salt spray resistant Example 1 Level 0 159.8° Level 1 excellent excellent excellent Example 2 Level 0 156.9° Level 1 excellent excellent excellent Example 3 Level 0 162.8° Level 1 excellent excellent excellent Comparative Example 1 Level 1 75.9° Level 2 qualified qualified qualified Comparative Example 2 Level 1 90.6° Level 2 qualified qualified qualified Comparative Example 3 Level 1 100.8° Level 2 qualified qualified qualified Comparative Example 4 Level 1 84.5° Level 2 qualified qualified qualified Comparative Example 5 Level 1 68.2° Level 3 Failure Failure Failure
[0187] It can be seen from the data in Table 1 that the coating formed by the present invention has excellent adhesion and super hydrophobicity compared with the comparative example, and has strong cleaning ability and is not easy to cause pollution. It has excellent acid resistance, alkali resistance, and salt spray resistance, and can be used in buildings, cross-sea bridges, ships and other places that are subject to long-term rain erosion and seawater corrosion.
[0188] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A super hydrophobic antifouling self-cleaning coating, characterized in that: It includes the following components by weight: The modified graphene oxide is prepared by modifying graphene oxide with γ-methacryloxypropyltrimethoxysilane; The modified nano silicon dioxide is prepared by modifying silicon dioxide with octyltriethoxysilane and nonafluorohexyltriethoxysilane.
2. A super hydrophobic antifouling self-cleaning coating according to claim 1, characterized in that, The modified graphene oxide is prepared by the following steps: Graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution are uniformly mixed, stirred and filtered to obtain modified graphene oxide.
3. A super hydrophobic antifouling self-cleaning coating according to claim 2, characterized in that, The mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:(1-5):(100-300); And / or, the mass ratio of anhydrous ethanol to water in the ethanol aqueous solution is 1:1; And / or, the specific conditions of the stirring are: Stir at 400-800 rpm for 4-8 hours at 50-80°C.
4. A super hydrophobic antifouling self-cleaning coating according to any one of claims 1 to 3, characterized in that: The modified nano silicon dioxide is prepared by the following steps: Octyltriethoxysilane and nonafluorohexyltriethoxysilane are dissolved in ethanol, the pH is adjusted to 4-6, and stirred for a primary reaction to obtain a liquid phase. Then, silicon dioxide is dispersed in ethanol and added to the liquid phase, the pH is adjusted to 10-12, and stirred for a secondary reaction. After centrifugal washing and drying, modified nano silicon dioxide is obtained.
5. A super hydrophobic antifouling self-cleaning coating according to claim 4, characterized in that: The mass ratio of the octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:(4-8); And / or, the time of the primary reaction is 30-40 minutes and the temperature is 20-40°C; And / or, the reagent used to adjust the pH to 4-6 is acetic acid, and the solvent used to adjust the pH to 10-12 is ammonium hydroxide; And / or, the secondary reaction time is 18-36h and the temperature is 20-40°C.
6. A super hydrophobic antifouling self-cleaning coating according to any one of claims 1 to 5, characterized in that: The fluorocarbon resin is one or more of HLR-6, HLR-7, HLR-670, ZHM-2, ZHM-5, and ZHM-70; and / or, the curing agent is one or more of aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; and / or, the dispersant is one or more of BYK-110, BYK-161, Nuosperse FX600, SDA120, SDA-150, SDA-170; And / or, the leveling agent is one or more of EFKA-3777, HY-3777, FC-4430, and AKN-1377; And / or, the defoamer is a higher alcohol defoamer or an organosilicon defoamer; And / or, the solvent is one or more of xylene, butyl acetate, propylene glycol methyl ether acetate, and ethylene glycol ethyl ether acetate.
7. A method for preparing a super hydrophobic antifouling self-cleaning coating, characterized in that: The following steps are involved: S1, mixing graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution uniformly, stirring and filtering to obtain modified graphene oxide; S2, dissolving octyltriethoxysilane and nonafluorohexyltriethoxysilane in ethanol, adjusting the pH to 4-6, stirring for a primary reaction to obtain a liquid phase, dispersing silicon dioxide in ethanol and adding it to the liquid phase, adjusting the pH to 10-12, stirring for a secondary reaction, and centrifugally washing and drying to obtain modified nano-silicon dioxide; S3, 20-50 parts of fluorocarbon resin and 30-60 parts of solvent are mixed evenly, and then 5-15 parts of curing agent, 1-5 parts of dispersant, 1-5 parts of leveling agent, 1-5 parts of defoaming agent, 1-10 parts of modified graphene oxide and 1-10 parts of modified nano-silica are added under stirring, and mixed evenly to obtain a super hydrophobic antifouling self-cleaning coating.
8. A method for preparing a super hydrophobic antifouling self-cleaning coating according to claim 7, characterized in that: In step S1, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:(1-5):(100-300); and / or, in step S1, the mass ratio of the graphene oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 1:2:200; And / or, in step S1, the mass ratio of anhydrous ethanol to water in the ethanol aqueous solution is 1:1; And / or, in step S1, the specific conditions of the stirring are: Stir at 400-800 rpm for 4-8 hours at 50-80°C.
9. A method for preparing a super hydrophobic antifouling self-cleaning coating according to claim 7, characterized in that: In step S2, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:(4-8); And / or, in step S2, the mass ratio of octyltriethoxysilane, nonafluorohexyltriethoxysilane and silicon dioxide is 1:1:6; And / or, in step S2, the time of the primary reaction is 30-40 min, and the temperature is 20-40° C.; And / or, in step S2, the reagent used to adjust the pH to 4-6 is acetic acid, and the solvent used to adjust the pH to 10-12 is ammonium hydroxide; And / or, in step S2, the secondary reaction time is 18-36 hours and the temperature is 20-40°C.
10. A method for preparing a super hydrophobic antifouling self-cleaning coating according to claim 7, characterized in that: In step S3, the fluorocarbon resin is one or more of HLR-6, HLR-7, HLR-670, ZHM-2, ZHM-5, and ZHM-70; and / or, in step S3, the curing agent is one or more of aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; and / or, in step S3, the dispersant is one or more of BYK-110, BYK-161, Nuosperse FX600, SDA120, SDA-150, and SDA-170; And / or, in step S3, the leveling agent is one or more of EFKA-3777, HY-3777, FC-4430, and AKN-1377; And / or, in step S3, the defoamer is a higher alcohol defoamer or an organosilicon defoamer; And / or, in step S3, the solvent is one or more of xylene, butyl acetate, propylene glycol methyl ether acetate, and ethylene glycol ethyl ether acetate.
Citation Information
Patent Citations
Nanometer fluorocarbon modified coating with titania, its production and process
CN100554343C
A fluorocarbon coating, its preparation method and application
CN113637368B
Super-hydrophobic loofah sponge for separating oil and water and preparation method thereof
CN106883588A
Self-healing type super-amphiphobic and photocatalytic double self-cleaning coating and method for preparing same
CN109082230A
Modified graphene oxide co-curing water-borne epoxy resin paint and preparation method thereof
CN110054965A
Cited By
Fluorosilane modified PVDF coating and preparation method thereof
CN120574503A
Modified graphene oxide water-based organic silicon coating, preparation method thereof and organic silicon coating
CN121203533A